The Analysis of R&D Impact on the Public Listed Companies’ Performance in Indonesia - Natasha I. E.; Yanthi R. I. Hutagaol (Bina Nusantara University, 2009)
Research & Development (R&D) is one of significant firms’ activities that is expected to enhance firms’ future value. This paper examines the relationship between R&D with firm’s operation and market performance. The sample used is 106 firm years from 32 non-finance firms that listed in Indonesia Stock Exchange (IDX) and report R&D expenditure during period 2004-2007. Two research hypotheses are developed and tested using a multiple regression model. The findings signify that all sample firms have reported their R&D activities accordingly to the applied accounting standard. However, the hypothesis testing results shows that there is no relationship between R&D and firm’s operation and market performance. These findings imply that R&D activities in Indonesian firms are not yet perceived as an important element in firms’ value added chain.